Potential clinical variants detected in mitochondrial DNA D-loop hypervariable region I of patients with non-alcoholic steatohepatitis - EREN, FATİH; YILMAZ, YUSUF (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
Purpose Non-alcoholic steatohepatitis (NASH) is a mitochondrial disease. However, the underlying role of mitochondrial genetics has not yet been completely elucidated. Evaluation of D-loop nucleotide variations with respect to statistical significance and clinical data distribution. Methods Genomic DNAs were extracted from the peripheral blood samples of patients with biopsy-proven 150 NASH as well as from 150 healthy individuals to explore the functional D-loop region responsible for the replication and transcription of the mitochondrial genome. DNA sequencing by capillary electrophoresis analysis was performed for the D-loop region of mitochondrial DNA containing the hypervariable region I, and restriction fragment length polymorphism with MnlI analysis was performed for the m.16189 T/C D-loop variant. Results The m.A16318C variant was detected only in patients with NASH and approached significance level. Based on clinical data, six variants associated with histological subgroups of NASH and NASH-complicated diseases were identified. In patients with NASH, the m.16129 AA genotype was associated with advanced-stage fibrosis; the m.16249 CC genotype was associated with advanced lobular inflammation and advanced-stage histological steatosis; the m.16296 TT genotype was associated with hypothyroidism; the m.16163 GG and m.16294 TT genotypes were associated with metabolic syndrome; and the m.16256 TT+CT genotypes were associated with type II diabetes. In patients with NASH, microRNAs were estimated by targeting the significant variants identified in this study. Conclusion These findings suggest that NASH may be associated with D-loop nucleotide variations and that microRNA-based in vitro and/or in vivo studies may be developed by targeting the D-loop variants.
Keywords: D-loop; MicroRNA target prediction; Mitochondrial DNA; Non-alcoholic steatohepatitis; Non-alcoholic fatty liver disease; Polymorphism; TYPE-2 DIABETES-MELLITUS; FATTY LIVER-DISEASE; SCORING SYSTEM; ASSOCIATION; DYSFUNCTION; TRACT